2020
DOI: 10.1093/eurpub/ckaa019
|View full text |Cite
|
Sign up to set email alerts
|

Do healthy doctors deliver better messages of health promotion to their patients?: Data from the SUN cohort study

Abstract: Background Healthy lifestyle adherence is associated with lower chronic disease morbidity/mortality. The role of doctors, as counselors and role models, is essential. Among physicians participating in a prospective cohort, we investigated the behavioral counseling on diet and lifestyle provided to their patients in association with their own personal behaviors. Methods We assessed 890 doctors aged ≤65 years participating in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…In this context, a previous study conducted in this same sample of doctors found that prescribing practices were associated other forms of behavioural counselling. 13 Our study showed that age or sex of the physician was not associated with counselling of screening cancer in general. These results are similar to those that Engler et al found in their study where no differences were found between male and female physicians regarding rating the cancer screening examination as useful or fairly useful, 27 and Lofters et al found no differences between physicians' age and the counselling of cancer screening.…”
Section: Smokingmentioning
confidence: 53%
See 2 more Smart Citations
“…In this context, a previous study conducted in this same sample of doctors found that prescribing practices were associated other forms of behavioural counselling. 13 Our study showed that age or sex of the physician was not associated with counselling of screening cancer in general. These results are similar to those that Engler et al found in their study where no differences were found between male and female physicians regarding rating the cancer screening examination as useful or fairly useful, 27 and Lofters et al found no differences between physicians' age and the counselling of cancer screening.…”
Section: Smokingmentioning
confidence: 53%
“…In this context, a previous study conducted in this same sample of doctors found that prescribing practices were associated other forms of behavioural counselling. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily stresses due to economic hardship, unemployment, family conflict, lack of public spaces for recreation and leisure and lack of sustainable facilities for physical activities, all increase the stress and ultimately their impact on NCD risk 71. Interventions to promote healthy behaviours among students were positively associated with their prevention-related attitudes and counselling practices 35 66 72 73. Thus, appropriate interventions can be implemented to improve the health and well-being of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is responsible for more than 6 million deaths worldwide each year ( 2 ). Because physicians are the primary sources of health knowledge and medical advice ( 3 ), and their medical advice has a large impact on the population's health perceptions and health behaviors. The World Health Organization encourages and mobilizes health professionals to become actively involved in tobacco harm prevention and control ( 4 ).…”
Section: Introductionmentioning
confidence: 99%